2007
DOI: 10.1002/mnfr.200600213
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and antifibrogenic effects of s‐ethyl cysteine and s‐methyl cysteine in the kidney of diabetic mice

Abstract: Protective effects of s-ethyl cysteine (SEC) and s-methyl cysteine (SMC) in kidney of diabetic mice were examined. SEC and SMC at 0.5, 1, 1.5, 2 g/L were added to the drinking water for 6 wk. Results showed that the intake of SEC or SMC alleviated body weight loss and urine output, as well as markedly decreased plasma blood urea nitrogen (BUN) and creatinine clearance (CCr) in diabetic mice (P < 0.05). The intake of SEC caused significantly dose-dependent increase in insulin and decrease in blood glucose, urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 28 publications
0
46
0
1
Order By: Relevance
“…However, the study of Melhem et al [26] and our present study revealed that ascorbic acid was not an effective agent against diabetic renal glycative injury. Our previous study has indicated that the dietary intake of SEC and SPC in diabetic mice alleviated BW loss and urine output, decreased plasma BUN and CCr, suppressed renal protein kinase C Data are mean l SD, n = 15; p a 0.05. activity, and renal TGF-beta1 mRNA expression [13,14]. Therefore, we concluded that SEC and SPC, cysteine-containing compounds naturally derived from Allium plants, were potent agents for attenuating diabetic renal injury.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, the study of Melhem et al [26] and our present study revealed that ascorbic acid was not an effective agent against diabetic renal glycative injury. Our previous study has indicated that the dietary intake of SEC and SPC in diabetic mice alleviated BW loss and urine output, decreased plasma BUN and CCr, suppressed renal protein kinase C Data are mean l SD, n = 15; p a 0.05. activity, and renal TGF-beta1 mRNA expression [13,14]. Therefore, we concluded that SEC and SPC, cysteine-containing compounds naturally derived from Allium plants, were potent agents for attenuating diabetic renal injury.…”
Section: Discussionmentioning
confidence: 89%
“…It is known that renal VEGF could be regulated by oxidative stress, AGEs, cytokines, and TGF-beta1 [6,33]. Our previous study already indicated that SEC could markedly improve renal oxidative stress and blunt renal TGF-beta1 expression [14].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Renal tissue was homogenized in 10 mmol/L Tris–HCl buffered solution (pH 7.4) containing 2 mol/l NaCl, 1 mmol/l EDTA, 0.01% Tween 80, 1 mmol/l PMSF, and centrifuged at 9000 × g for 30 min at 4°C [14]. The resultant supernatant was used for cytokine determination.…”
Section: Methodsmentioning
confidence: 99%
“…The deficiency of this essential element increases the osmotic fragility of erythrocyte membranes and the levels of lipid peroxidation in mitochondrial and microsomal membranes, while the presence of zinc prevents lipid peroxidation 5 . In addition, the antioxidant activity of the amino acid Smethyl-L-cysteine has been reported 10 . It prevents the oxidation of species from lipid hydroperoxide (LOOH) during formation of the human low-density lipoprotein (LDL) 11 .…”
Section: Introductionmentioning
confidence: 99%